Risk factors, screening tests and prevention strategies of muscle injuries in élite soccer players: a critical review of the literature - Francavilla, V. C.; Bongiovanni, T.; Todaro, L.; Genovesi, F.; Francavilla, G. (Medicina dello Sport, 2016)
The study of the risk factors, screening tests and especially of prevention strategies of muscle injuries is going through a period of great scientific interest, the indisputable testimony is represented by the great numbers of studies available in literature. However, some basic aspects of the problem as, in our view, the real difficult in identifying valid risk factors, the use of screening tests validated and reliable and preventative strategies to be implemented, which vary from club to club, must still be perfectly clarified, and this has to date limited the development of unanimously agreed guidelines.